Survey of Forest Elephants Loxodonta cyclotis (Matschie, 1900) (Mammalia: Proboscidea: Elephantidae) in the Bia Conservation Area, Ghana - Emmanuel Danquah; Samuel K. Oppong (Journal of Threatened Taxa, 2014)
Information on elephant ranges and numbers is vital for effective conservation and management, especially in western Africa where elephant populations are small and scattered.  The Bia Conservation Area (BCA) in southwestern Ghana is a priority site for the conservation of Forest Elephants in western Africa.  A dung count was conducted using a systematic segmented track line design to determine the density and distribution of the BCA elephant population.  The mean density of dung-piles was 452.15 per sq.km. and mean dung survival time was estimated to be 54.64 days (SD 2 days), leading to an estimate of 146 elephants (95% confidence interval 98-172) with a density of 0.48/km2 for the BCA. This estimate probably makes the Bia forest elephant population the largest in Ghana.  Records of BCA elephant activities were also made.  This study augments the Regional African Elephant Database and should facilitate strategic planning and management programmes.